Exploring the emergence of scientific ethics in inquiry-based renewable energy learning: a case study in elementary school - Azizah, Nurul; Suciptaningsih, Oktaviani Adhi; Rufiana, Intan Sari; Anggraini, Ade Eka; Mardhatillah (Jurnal Bidang Pendidikan Dasar, 2026)
This study explores the emergence of scientific ethics through inquiry-based renewable energy learning among fifth-grade elementary students. While inquiry-based learning (IBL) is widely recognized for improving scientific literacy and conceptual understanding, its role in fostering scientific ethical values at the elementary level remains underexplored. Using a qualitative case study design at SDN Ciptomulyo 1 Malang City, data were collected through participant observation, in-depth interviews, and documentation, and analyzed thematically. The findings indicate that inquiry activities involving experiments with mini solar panels and windmills fostered honesty in data recording, responsibility in conducting procedures, openness to empirical evidence, collaborative engagement, and critical reflection on experimental outcomes. These ethical dispositions emerged through structured investigation and teacher-facilitated discussion. The study highlights that inquiry-based renewable energy instruction not only enhances conceptual mastery but also supports the development of scientific character in elementary science education.